Mate recognition in Acanthagrion truncatum (Odonata: Coenagrionidae) - doi: 10.4025/actascibiolsci.v35i3.16138 (Acta Scientiarum. Biological Sciences, 2013)
Sexual and species recognition, along with sexual color dimorphism, play an important role in the reproduction of many animal species. In this article, it was investigated if males of the dimorphic Neotropical damselfly Acanthagrion truncatum are able to recognize mates and differentiate them between co-specific males and hetero-specific females of sympatric species. The results showed misguided mating attempts from males towards other males and Homeoura chelifera females. They also seem able to recognize A. lancea and Telebasis carmesina females as hetero-specifics. This study support the hypothesis that male-male interactions are misdirected sexual behavior and that sympatric morphologically similarspecies may represent visual interference for mate searching males.